Five Questions to Understand Epistemology and Its Influence on Integrative Marine Research - Moon, Katie; Cvitanovic, Christopher; Blackman, Deborah A.; Scales, Ivan R.; Browne, Nicola K. (Frontiers in Marine Science, 2021)
Developing solutions to the complex and uncertain problems facing marine and coastal social-ecological ecosystems requires new forms of knowledge production and integration. While progress has been made both in terms of successfully producing integrated marine research and connecting that knowledge to decision-makers, a number of significant challenges remain that prevent the routine development and implementation of successful integrated research practice. Based on our own experiences as social researchers working within interdisciplinary research teams, we contend that one of the main barriers to successful integrative marine research relates to understanding, and where possible reconciling, the different epistemologies that unpin how knowledge is created or discovered in different disciplines. We therefore aim to provide an accessible introduction to the concept of epistemology, with a focus on its importance and influence to integrated marine research practice. Specifically, we present and discuss five questions of research design that relate to epistemology in integrative research practices: (1) What is the object of study we seek to create knowledge about; (2) how do we create knowledge; (3) who accepts knowledge as ‘true’ and how?; (4) how do we determine the epistemology underpinning marine science; and (5) what are the implications of epistemology for applied integrative marine science? We demonstrate the application of each question through a hypothetical case study of marine restoration, focusing on coral transplanting. Finally, we offer readers a simple heuristic to guide them, irrespective of career stage or discipline, to understand and account for epistemology when participating in integrative marine research practices.